Determinants of Trade Credit Supply among Developing Countries during the Financial Crisis of 2008 - Bashir, Rabia; Regupathi, Angappan (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The purpose of this study is to identify the firm-specific and country-specific determinants of trade credit supply during the financial crisis of 2008 and compare among upper-middle income and lower-middle income countries. Trade credit supply is measured as average collection period. For panel data analysis, this study uses the Prais - Winsten Panel Corrected Standard Errors (PCSE) method. PCSE removes the of cross-sectional dependence issue in the panel dataset. Findings indicate that firms had to pay their suppliers earlier during the financial crisis 2008 than pre-crisis. Financial crisis significantly influenced the relationship between determinants and trade credit supply but to different levels in different income groups. Average payment periods and private credit to GDP significantly and positively increased the average collection period more in lower-middle income developing countries and less in upper-middle developing income countries. Cash flow volatility and leverage influenced the average collection period significantly and negatively during the crisis. This influence was stronger than pre-crisis and post-crisis periods, and more significant in lower-middle income countries and less in upper-middle income countries. The negative relationship between inflation and trade credit supply is strongly negative in lower-middle income countries. Overall, the results suggest that financial crisis changed the relationship between determinants and trade credit supply and the extant of this change was different in different income group countries.